Příspěvek na péči jako „zvláštní peníze“: chápání a užívání příspěvku na péči v blízkých vztazích - Radka Dudová (Gender a Výzkum)
The paper presents the comparative results of two qualitative researches on long-term informal family care in the Czech Republic: one researching the life strategies of women caring for their elderly parents and the other researching women caring for a child with a disability. The interviews with the two groups of caregivers make it possible to compare the ways in which people in different caring situations interpret and use the same state benefit intended for people who need personal long-term care. The analysis shows how the individual understanding of the same benefit is shaped by cultural values and norms, leading to the use of the money in distinct ways, which then has specific consequences for the economic situation of caring women. While the mothers caring for a disabled child view the benefit as their work income, which they are entitled to by the fact that they are providing care, the caring daughters (and sons) understand the allowance as money that belongs to their elderly parent and earmark it for the parent´s special needs. They do not interpret or use this money in accordance with the intentions of policy-makers because they fear they could be accused of commodifying the care or breaching the norm of intergenerational solidarity. I therefore argue that different situations of care require different policy solutions. In the situation of care for an elderly parent, in the context of a country with strong norms of intergenerational solidarity and a high proportion of informal care, the measures of financial support for end users have proved ineffective as financial support for caregivers.